Protagonists of the battles: Angola’s black army - Carvalho da Cruz, Ariane (Revista Crítica Histórica, 2022)
This article aims to analyze the black army, the largest contingent present in military campaigns in Angola in the eighteenth century. The importance of this troop was confirmed by the specialized historiography, which highlighted the need for recognition of local Central African forces and the establishment of political alliances for successful campaigns. The black army was the main demographic element of the military ranks, which made local warfare customs prevail, even in the campaigns initiated by the Portuguese government. Without this, it was impossible for Portuguese governments to form troops and wage wars. Considering the centrality of this troop, we aim to better understand the elements that compose it, the political titles, their hierarchies, the discourses, and memories about this military force.